Asymmetric Homogeneous Hydrogenation of α-Dicarbonyls using new Rhodium Catalyst - Singh, R.P. (Asian Journal of Chemistry, 2010)
Asymmetric homogeneous hydrogenations of α-keto esters and α-keto amides of the types PhCOCO2ME, PhCOCO2Et, PhCOCONHCH2Ph, PhCH2CH2COCO2Et and PhCOCONEt2 have been carried out under mild conditions using new cationic rhodium catalyst (6) with cyclohexylated diphosphine ligand.